External Effects of Education: Human Capital Spillovers in Regions and Firms - Thomas K. Bauer; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Using a matched employer-employee panel dataset for Germany, we analyze the external effects of education on individual wages. Following the basic framework of Moretti (2004), we allow spillover effects to occur both within a specific firm and a specific region rather than analyzing spillover effects only on a regional level. Controlling for individual- and firm-specific fixed effects and using an instrumental variable strategy, our results confirm the existence of positive but small external effects of human capital. Positive spillover effects within firms occur only for the group of high-skilled workers. – – Der Artikel untersucht mithilfe des Linked Employer-Employee Datensatzes des IAB (LIAB), ob in Deutschland externe Effekte höherer Bildung auf individuelle Einkommen existieren. Das ökonometrische Verfahren lehnt sich eng an Moretti (2004) an und erlaubt das Auftreten externer Effekte in Firmen und auf regionaler Ebene. Unter Verwendung individueller und firmenspezifischer fixer Effekte und Instrumentvariablenschätzern bestätigen unsere Ergebnisse das Vorliegen externer Effekte von Humankapital. Die gefundenen Effekte sind positiv, wenn auch quantitativ eher gering. Positive externe Effekte innerhalb von Firmen treten nur bei der Gruppe der hochqualifizierten Arbeitnehmer auf.
Keywords: C23; D62; J31; 330; external effects; human capital; employer-employee matched data